2012
DOI: 10.1086/666828
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Signaling: Evolutionary Origins of the Immune-Modulating Effects of Dietary Fat

Abstract: Many dietary fatty acids (FA) have potent effects on inflammation, which is not only energetically costly, but also contributes to a range of chronic diseases. This presents an evolutionary paradox: Why should the host initiate a costly and damaging response to commonly encountered nutrients? We propose that the immune system has evolved a capacity to modify expenditure on inflammation to compensate for the effects of dietary FA on gut microorganisms. In a comprehensive literature review, we show that the body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 231 publications
(278 reference statements)
0
19
0
1
Order By: Relevance
“…For example, ARA was shown to improve the survival and reproduction of D. magna exposed to an opportunistic bacterial pathogen (Schlotz et al 2014). However, in vertebrates, ARA-and EPAderived eicosanoids have partially opposing effects, where their proinflammatory and anti-inflammatory activity, respectively, serves as the best example (Schmitz and Ecker 2008;Alcock et al 2012). The possible inhibition of the synthesis of ARA-derived eicosanoids by EPA (Sargent et al 1999;Schmitz and Ecker 2008) led to the assumption that the actions of eicosanoids in fish physiology depend on the ratio of EPA and ARA in the tissue (Koussoroplis et al 2011).…”
Section: Intersection Points Of the Saturation Curves And Potential Cmentioning
confidence: 99%
“…For example, ARA was shown to improve the survival and reproduction of D. magna exposed to an opportunistic bacterial pathogen (Schlotz et al 2014). However, in vertebrates, ARA-and EPAderived eicosanoids have partially opposing effects, where their proinflammatory and anti-inflammatory activity, respectively, serves as the best example (Schmitz and Ecker 2008;Alcock et al 2012). The possible inhibition of the synthesis of ARA-derived eicosanoids by EPA (Sargent et al 1999;Schmitz and Ecker 2008) led to the assumption that the actions of eicosanoids in fish physiology depend on the ratio of EPA and ARA in the tissue (Koussoroplis et al 2011).…”
Section: Intersection Points Of the Saturation Curves And Potential Cmentioning
confidence: 99%
“…, unsaturated fatty acids had a higher anti‐microbial effect compared with SFA and within the group of SFA, short‐chain saturated FA (4–12 carbons in length) had a higher bactericidal effect, compared with long‐chain saturated FA (more than 12 carbons). Furthermore, while MUFA had a lower anti‐microbial effect then PUFA of the same chain length, the n‐3 PUFA had a greater effect compared with n‐6 PUFA, but the results are not consistent . Although human evidence is scarce, research showed that the type of dietary fat has an effect on the faecal microbiota.…”
Section: The Intestine and Gut Microbiota In Insulin Resistancementioning
confidence: 99%
“…Research has shown that FAs exert their effect on bacterial growth and survival, in part, via altering the microbial cell membrane fluidity and disrupting cell membranes of certain bacteria (608,609). As reviewed by Alcock et al (610), unsaturated fatty acids had a higher antimicrobial effect compared with SFA and within the group of SFA, short-chain saturated FA (4-12 carbons in length) had a higher bactericidal effect, compared with long-chain saturated FA (more than 12 carbons). Furthermore, while MUFA had a lower anti-microbial effect then PUFA of the same chain length, the n-3 PUFA had a greater effect compared with n-6 PUFA, but the results are not consistent (610).…”
Section: Putative Nutritional Targets To Modulate Gut Microbiota Compmentioning
confidence: 99%
“…Eicosanoids are involved in reproduction, ion transport physiology and an array of defence mechanisms in vertebrates and invertebrates (Stanley, ). In vertebrates, n‐6 long‐chain PUFAs are considered to predominantly mediate pro‐inflammatory processes and n‐3 PUFAs are deemed to be their anti‐inflammatory counterparts (Calder, ; Schmitz & Ecker, ; Alcock et al ., ). Whether n‐6 and n‐3 PUFAs can be assigned similarly to differential functions with opposing outcome in invertebrates has not yet been conclusively investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Disturbance of this natural balance between host and gut microbiota, however, may facilitate growth and establishment of opportunistic pathogens (Stecher & Hardt, ). Differences in lipid‐mediated food quality can strongly influence the fitness of consumers and affect the gut microbiota (Scott et al ., ), may affect the outcome of host–parasite interactions (Schlotz et al ., ), and even provide signals for the host inflammatory machinery (Alcock et al ., ). At the same time, there is evidence that some Pseudomonas species have the potential to modulate eicosanoid production of its host, thereby interfering with the host's defence mechanisms (Vance et al ., ).…”
Section: Introductionmentioning
confidence: 97%